A people destroyed new research on the Roma genocide, 1941-1945 - Weiss-Wendt, Anton 1973- (University of Nebraska Press, 2025)
Anton Weiss-Wendt and the volume's contributors build on extensive existing Holocaust scholarship to feature the most recent work on the Roma genocide in Europe during World War II.